Ectoparasitos em murídeos sinantrópicos (Rodentia) em Pelotas, sul do Rio Grande do Sul, Brasil - Winkel, Kathleen Tavares (2013)
The murine Mus and Rattus play an important role in the transmission of diseases, both for humans and for livestock, either on his urine, feces , bites or through their ectoparasites. Considering the role played by ectoparasites of synanthropic rodents as vectors and / or reservoirs of disease, this study aimed to survey the ectoparasite fauna as well as to estimate the prevalence, abundance and mean intensity of ectoparasites in rodents captured in Pelotas, southern Rio Grande do Sul, Brazil. In the period January to May 2013 was conducted to capture sinantropic Murid (Rodentia) living through Tomahawk® traps that were exposed 22h to 7h, baited with cubes of bacon, replenished daily. The traps were placed in the port area and was taken to capture as laboratory Insect Biology DEMP/IB/UFPEL. Was captured 48 murine Mus musculus 6, Rattus rattus 7 and Rattus norvegicus 35, which were euthanized and placed in containers of water and detergent for 20 minutes after it was performed by brushing the search for ectoparasites. Obtaining a total of 6791 specimens belonging to Acari (65.4%), Anoplura (34.3%), and Siphonaptera (0.3%). No significant correlation regarding sex and weight of the hosts with the number of specimens and species of ectoparasites. The species of arthropod ectoparasites identified were Laelaps (Echinolaelaps) echidninus (Gamasida) Myocoptes musculinus (Acaridida) Radifordia lukoschusi (Actinedida), Ctenocephalides felis (Siphonaptera), Leptopsylla segnis (Siphonaptera) and Xenopsylla cheopis (Siphonaptera). Polyplax spinulosa (Anoplura) was the only species found in lice and Rhipicephalus sanguineus (Ixodida) the single tick. Polyplax spinulosa showed 100% prevalence in Rattus rattus and mean intensity of 175.83 in Rattus norvegicus, Radfordia lukoschusi showed the highest mean abundance 84.86 in Rattus rattus.